2011
DOI: 10.3168/jds.2010-4045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liquid retentate storage on flavor of spray-dried whey protein concentrate and isolate

Abstract: The objective of this study was to determine the effects of holding time of liquid retentate on flavor of spray-dried whey proteins: Cheddar whey protein isolate (WPI) and Mozzarella 80% whey protein concentrate (WPC80). Liquid WPC80 and WPI retentate were manufactured and stored at 3°C. After 0, 6, 12, 24, and 48h, the product was spray-dried (2kg) and the remaining retentate held until the next time point. The design was replicated twice for each product. Powders were stored at 21°C and evaluated every 4 mo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…In the United States, the 2 mains sources of liquid whey are Mozzarella and Cheddar. Liaw and others (2010) reported that Mozzarella and Cheddar liquid whey were distinct in flavor and volatile compounds initially but that Cheddar whey was also more prone to lipid oxidation than Mozzarella whey, and Whitson and others (2011) reported similar findings with liquid Mozzarella and Cheddar retentates. Mesophilic Lactococcus lactis starter cultures, used to produce Cheddar cheese, influenced flavor and oxidative stability of liquid whey (Carunchia Whetstine and others 2003; Tomaino and others 2004).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the United States, the 2 mains sources of liquid whey are Mozzarella and Cheddar. Liaw and others (2010) reported that Mozzarella and Cheddar liquid whey were distinct in flavor and volatile compounds initially but that Cheddar whey was also more prone to lipid oxidation than Mozzarella whey, and Whitson and others (2011) reported similar findings with liquid Mozzarella and Cheddar retentates. Mesophilic Lactococcus lactis starter cultures, used to produce Cheddar cheese, influenced flavor and oxidative stability of liquid whey (Carunchia Whetstine and others 2003; Tomaino and others 2004).…”
Section: Introductionmentioning
confidence: 83%
“…Wheys made from whole milk were expected to have higher cardboard flavor due to higher fat content and lipid oxidation. Previously, differences in the flavor of fluid whey have been attributed to different starter cultures, different processing techniques used to produce these cheeses and storage (Carunchia‐Whetstine and others 2003; Karagül‐Yüceer and others 2003; Gallardo‐Escamilla and others 2005; Liaw and others 2010; Whitson and others 2011). The current study demonstrated that fat content, culture, and storage time all contributed to flavor differences in whey.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Cheddar whey may be more prone to off‐flavor development during processing into whey protein compared to Mozzarella whey, independent of downstream processing differences that may occur. Whitson and others (2011) recently demonstrated that more degradation occurred in Cheddar whey retentates compared to Mozzarella whey retentates during cold storage even when fat content was higher in the Mozzarella retentate. Studies with commercial WPCs have also suggested that whey proteins from Mozzarella and Cheddar wheys are distinct in flavor initially and after storage of dried product (Wright and others 2009; Campbell and others 2011a, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Volatile lipid oxidation compounds, including C 6 –C 14 aldehydes, have been identified in nonfat dry milk, whey protein isolate and whey protein concentrate . Hexanal accounted for over 90% of total aldehydes in the latter two products . This high concentration of hexanal was believed to result from the oxidation of linoleic acid of phospholipids.…”
Section: Phospholipids In Lipid Oxidationmentioning
confidence: 99%